AI in healthcare: Weighing innovation with trust, ethics, and human touch - Talat Waseem; Haseeb Arif (Journal of Shalamar Medical & Dental College, 2025)
Artificial Intelligence (AI) is a game-changing phenomenon that has the potential to change how we communicate, work, and live completely. This is particularly true for the healthcare industry, where artificial intelligence (AI) has been applied to a wide range of fields, including medical education and training, diagnostic medicine, creating individualized treatment plans, and medical research, which has produced advances in essential fields like pharmacology and genomics.1 But as AI technology develops and becomes increasingly integrated into our daily lives, it is essential to comprehend how it affects society's socioeconomic elements and the moral and societal conundrums raised by its broad use.